Factors Influencing Purchase Intention Against Marketplace Users in Gen Z: Factors Influencing Purchase Intention Against Marketplace Users in Gen Z - Ika Tirta Candra Rini (SMARTINDO, 2023)
purpose- The weakness of the marketplace is that it cannot physically present products that can be touched by potential customers, for this reason information liaison is needed including influencers and product features to increase consumer purchase intentions. The marketplace itself has become a lifestyle, especially for the Z generation (Gen Z) in buying a product. Design/methodology/approach -This study used a quantitative method by distributing 100 questionnaires, especially to the current Z generation, which is estimated to be in the age range of 20 to 40 years, who have certainly purchased products through marketplaces that have been determined by the researcher. By using the SPSS 25 analysis tool and the purposive sampling method. The results and techniques will describe several factors such as influencers, product features and lifestyle in influencing purchase intention. Findings and Discussions -From the results of calculations using the analytical tools applied to this study, it proves that influencers have a significant influence on purchase intention because consumers not only need the benefits of product features, but those that are closest to their satisfaction and needs that are deemed appropriate to support their lifestyle. Therefore, how important it is for companies to select influencers who can influence consumer buying interest by looking at the elements of good interaction between prospective consumers and their educators. With the aim of increasing more buying interest. For marketplace providers and their users, including producers who work together, they must always provide feature products that are always innovating where feature products are required to approach consumer satisfaction and needs. Conclusion- Marketplace is one of the most popular services for generation z at this time. Not only providing services anytime and anywhere regarding information on a product being traded, but also providing some interesting promotions. However, the marketplace also has several drawbacks because the service is only listed on the internet screen so consumers cannot see or physically touch the product to be purchased. For this reason, influencers are needed as a liaison and to increase consumer confidence by educating how to use and practice these products. There is interaction between influencers and consumers so that it influences the lifestyle of marketplace users as well as wanting to be recognized as part of an idol in using the same product.